Management of Breast Engorgement Through Breastfeeding Techniques and Breast Care: A Case Study - Lisa Rahmawati; Jumkar Dila; Elda Yusefni (CV. CENDIKIA JENIUS INDONESIA, 2026)
Breast engorgement is one of the most common breastfeeding problems experienced by postpartum women due to inadequate breast emptying. This condition may cause breast pain, swelling, impaired milk flow, and an increased risk of mastitis if not managed appropriately. Comprehensive midwifery care is therefore essential to manage breast engorgement while supporting the successful implementation of exclusive breastfeeding. Objective: This study aimed to describe the implementation of comprehensive midwifery care for a postpartum woman with breast engorgement through breastfeeding technique education, breast care, and non-pharmacological management at the Koto Anau Public Health Center, Solok Regency. Methods: A descriptive case study design was employed. The subject was a postpartum woman who experienced breast engorgement on the third day after delivery. Data were collected through interviews, observation, physical examination, and documentation. Midwifery care was provided using the SOAP (Subjective, Objective, Assessment, and Plan) approach over three follow-up visits. Results: Following the implementation of comprehensive and continuous midwifery care, the mother's condition improved progressively. By the third visit, the breast engorgement had resolved, and the mother was able to continue exclusive breastfeeding successfully. Conclusion: Comprehensive midwifery care consisting of breastfeeding technique education, breast care, warm and cold compresses, and continuous support was effective in managing breast engorgement in a postpartum woman. These interventions may serve as effective promotive and preventive strategies to improve breastfeeding success and prevent breast engorgement during the postpartum period.